2023
DOI: 10.1177/17407745221146987
|View full text |Cite
|
Sign up to set email alerts
|

Partially clustered designs for clinical trials: Unifying existing designs using consistent terminology

Abstract: Introduction: Clinical trial designs based on the assumption of independent observations are well established. Clustered clinical trial designs, where all observational units belong to a cluster and outcomes within clusters are expected to be correlated, have also received considerable attention. However, many clinical trials involve partially clustered data, where only some observational units belong to a cluster. Examples of such trials occur in neonatology, where participants include infants from both singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…This is also known as the therapist effect 2 . In both cases, the correlation is induced by the treatment; such trials are also called individually randomized group therapy trials, and more recently have been referred to as individual randomized trials with post‐randomization clustering 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also known as the therapist effect 2 . In both cases, the correlation is induced by the treatment; such trials are also called individually randomized group therapy trials, and more recently have been referred to as individual randomized trials with post‐randomization clustering 3 …”
Section: Introductionmentioning
confidence: 99%
“…2 In both cases, the correlation is induced by the treatment; such trials are also called individually randomized group therapy trials, and more recently have been referred to as individual randomized trials with post-randomization clustering. 3 An example where the correlation arises from treatment in a group setting is a cluster randomized trial. In this case, outcomes of participants are nested within clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Individually randomized group treatment (IRGT) trials (also referred to as individually randomized trials with post-randomization clustering which can involve differential clustering in different trial arms) are becoming increasingly popular in public health research and biomedical studies. [1][2][3] In an IRGT trial, although individuals are randomized to different trial arms, clustering of outcomes arises in one or both conditions due to the nature of the treatment being either group-based (eg, a group-based psychological treatment) or delivered to multiple participants by the same individual (eg, surgeon). In some IRGT trials, no clustering of outcomes occurs in the control or usual care condition.…”
Section: Introductionmentioning
confidence: 99%
“…Roberts and Roberts (2005) derived an explicit sample size formula to simultaneously adjust for such complexities in planning IRGT trials; Teerenstra et al (2023) extended their formula to allow for a baseline measurement of the outcome in both IRGTs and other nested or crossed designs. In the special case where active group-based treatment is compared with ungrouped standard care, IRGT trials are also known as partially clustered designs (Bauer et al, 2008;Lange et al, 2023), in which only the ICC of outcome in the active treatment group is nonzero. Systematic reviews suggested that clustering induced by treatment delivery has often been overlooked at both the design and analytical stages in randomized trials (Pals et al, 2008(Pals et al, , 2011, which may have led to overoptimistic findings in published trial reports.…”
Section: Introductionmentioning
confidence: 99%